GPU implementations of scheduling heuristics for heterogeneous computing environments - Nesmachnow, Sergio (2011)
This work presents the application of parallel computing techniques using Graphic Processing Units to improve the effciency of scheduling heuristics for heterogeneous computing systems. The experimental evaluation of the proposed methods demonstrates that a signiffcant reduction on the computing times can be attained, allowing to tackle large scheduling scenarios in reasonable execution times.